NILAI-NILAI MORAL DALAM ADAT PERKAWINAN MELAYU KECAMATAN BAHOROK KABUPATEN LANGKAT PROPINSI SUMATERA UTARA - Hamidah, Hamidah (TAZKIR: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2014)
AbstractABSTRACT: This study aims to analyze the moral values in Malay traditional wedding at Bahorok Langkat District in North Sumatra Province, covering mating customs, and moral values contained in it. This study uses qualitative method. The determination of sampling is done by purposive informant. It is not determined the amount. The target is to get information to the point of saturation, so that there is no difference anymore information of informant. Data is collected using observation, interview techniques and documention. The technique ensures the validity of this study is using triangulation of data sources and methods. The data analysis model is Miles and Hubberman method using three step: the simplification of data, presentation of data, and drawing conclusions. The research finds that the Malay traditional wedding at Bahorok has through several stages, beginning from merisik, woo , connective promise , then berinai night and the next day is the ceremony procession that accompanied the dish tasted juadah, followed by a procession escorted the bride to the stage hempang rod, introductory martial arts, hempang pages, dance reception, and fan hempang. The next procession is going up the aisle with a slap and exchange event hall, followed by a procession of plain flour, rice meal - facing presence and in the end with berdimbar bath. In the event merisik and woo, it found the social values such as respect and respecting for the rights of girls (gender), the event promises contain connective value of loyalty. In the event there is a power struggle on berinai, event ceremony of religious contains values on fighting and spirit. The event usher the bride is value of respect and leadership values. In the event of symbolic, there is a fresh flour religious value, harmony, honesty, fighting, spirit and respect for the natural environment. There is a symbolic slap on the value of harmony, democracy and independence.Kata Kunci : Nilai, Moral, Perkawinan, Melayu